Living with intestinal stoma: the construction of autonomy for care Vivir con estoma intestinal: la construcción de la autonomía para el cuidado Viver com estoma intestinal: a construção da autonomia para o cuidado - Débora Poletto; Denise Maria Guerreiro Vieira da Silva (Universidade de São Paulo, 2013)
OBJECTIVE: to investigate the care undertaken in the health services for people with intestinal stoma, from the perspective of articulating the actions proposed in the Amplified and Shared Clinic, with a view to promoting autonomy. METHOD: qualitative study. Participants: 10 people who received a stoma, and their family members. Data was collected between 10th January and 30th June 2011, through two semi-structured interviews. Analysis was through the stages: anxiety, synthesis, theorization and recontextualization. RESULTS: presented in the categories: (1) the need to carry out stoma care; (2) receiving health support and care after discharge from hospital; (3) returning to daily activities and social reinsertion. CONCLUSION: the study identified common factors which influence the process of development of autonomy and the relationship which health professionals have with this achievement. OBJETIVO: conocer la atención ofrecida en los servicios de salud a las personas con estoma intestinal, en la perspectiva de la articulación de las acciones propuestas por la Clínica Ampliada y Compartida objetivando la promoción de la autonomía. MÉTODO: estudio cualitativo. Participantes: 10 personas que realizaron ostomía y sus familiares. Datos recolectados de 10 de enero a 30 de junio de 2011 por medio de dos entrevistas semiestructuradas. Análisis compuesto por las etapas: aprehensión, síntesis, teorización y recontextualización. RESULTADOS: presentados en categorías: (1) la necesidad de realizar el cuidado con el estoma; (2) recibiendo apoyo y atención en salud después del alta hospitalaria; (3) retornando a las actividades de lo cotidiano y la reinserción social. CONCLUSIÓN: el estudio identificó factores comunes que influyen en el proceso de desarrollo de la autonomía y en la relación que los profesionales de salud tienen en esa conquista. OBJETIVO: conhecer a atenção desenvolvida nos serviços de saúde em relação às pessoas com estoma intestinal, sob a perspectiva da articulação das ações propostas pela Clínica Ampliada e Compartilhada, visando a promoção da autonomia. MÉTODO: estudo qualitativo. Participantes: 10 pessoas que realizaram estomia e seus familiares. Dados coletados de 10 de janeiro a 30 de junho de 2011, por meio de duas entrevistas semiestruturadas. Análise composta pelas etapas: apreensão, síntese, teorização e recontextualização. RESULTADOS: foram apresentados em categorias: (1) a necessidade de realizar o cuidado com o estoma, (2) recebendo apoio e atenção em saúde após a alta hospitalar e (3) retornando às atividades do cotidiano e à reinserção social. CONCLUSÃO: o estudo identificou fatores comuns que influenciam o processo de desenvolvimento da autonomia e a atuação que os profissionais de saúde têm em face dessa conquista.